Towards mismatched DNA photoprobes and photoreagents: "elbow-shaped" Ru(ii) complexes. Issue 1 (16th November 2016) - Deraedt, Q.; Marcélis, L.; Loiseau, F.; Elias, B.
Abstract : Due to their potentially harmful consequences, the detection of mismatched DNA is a subject of high interest. In order to probe these DNA mismatches, we report new Ru(ii ) complexes, bearing "elbow-shaped" extended planar ligands based on an acridine or a phenazine core. Abstract : Due to their potentially harmful consequences, the detection of mismatched DNA is a subject of high interest. In order to probe DNA mismatches by means of luminescent sensitive Ru(ii ) complexes, "elbow-shaped" extended planar ligands based on an acridine or phenazine core have been synthesized (npp = naphtho[1, 2- b ]pyrido[3, 2- f ][1, 7]phenanthroline andbdppz = benzo[ h ]dipyrido[3, 2- a :2′, 3′- c ]phenazine). The photophysical studies revealed that [Ru(bpy)2 npp] 2+ (bpy = 2, 2′-bipyridine) allows emission from a 3 MLCTbpy/npp excited state, while the lowest 3 MLCT for [Ru(bpy)2 bdppz] 2+ shifts from a bright 3 MLCTbpy/b̲d̲p̲pz state towards a poorly luminescent 3 MLCTbdpp̲z̲ state, probably due to the formation of H-bonds with water molecules in the excited state. Studies of the complexes in the presence of DNA demonstrate that they strongly bind to polynucleotides. In the presence of single base mismatched hairpin oligonucleotides, while [Ru(bpy)2 npp] 2+ does not show remarkable sensitivity to the nature of the mismatch site, [Ru(bpy)2 bdppz] 2+ exhibits noticeably differential luminescence behavior correlated to the nature and stability of the mismatch compared to the well-matched sequence. Photooxidant analogues of these complexes were prepared, replacing bpy ancillary ligands by bpz (2, 2′-bipyrazine). A photo-induced electron transfer from dGMP and polynucleotides to the excited states of [Ru(bpz)2 npp] 2+ and [Ru(bpz)2 bdppz] 2+ is observed. These results emphasized the role of "elbow-shaped" Ru(ii ) complexes as promising candidates for the development of mismatch-sensitive DNA photoprobes.